PENGARUH ULASAN PRODUK DAN KEPERCAYAAN TERHADAP MINAT PEMBELIAN ULANG YANG DIMEDIASI OLEH KEPUASAN KONSUMEN PADA MARKETPLACE SHOPEE DI SURAKARTA - Alfatah, Sultan Adam; Irmawati, Irmawati (JURSIMA, 2022)
The aim of this research is to analyze the influence of product reviews and trust on repurchase intention which is mediated by consumer satisfaction on the Shopee marketplace in Surakarta. The method used in this research is a quantitative method using non-probability sampling techniques, where researchers use a population of consumers who have made purchases with the Shopee marketplace in the Surakarta area. The data analysis technique used is External Model Analysis which includes convergent validity test, discriminant validity and reliability test, as well as using internal model analysis techniques which include R-squared, effect size (F-squared), predictive importance (Q-squared), testing hypothesis and testing. path coefficient. The research results show that product reviews have a positive effect on repurchase interest, trust does not have a positive effect on repurchase interest, product reviews have a positive effect on consumer satisfaction, trust has a positive effect on consumer satisfaction, consumer satisfaction does not have a positive effect on repurchase interest, consumer satisfaction does not succeeded in conveying the influence of product reviews on repurchase interest, and consumer satisfaction was unable to convey confidence in repurchase interest.